A review of food texture modification among individuals with cerebral palsy: the challenges among cerebral palsy families - Kamal, Sakinah; Kamaralzaman, Sazlina; Sharma, Shobha; Jaafar, Nurul Hazirah; Phei, Ming Chern; Hassan, Nurul Izzaty; Toran, Hasnah; Ismail, Noor Akmal Shareela; Yusri, Ghazali; Hamzaid, Nur Hana (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Individuals with cerebral palsy (CP) frequently present with multiple feeding problems, which may require food texture modification to ensure safe feeding. This review aims to explore the challenges individuals with CP and their caregiver’s face and recommend modified food textures to ensure safety and improve the quality of life and nutritional status. A systematic search was carried out through four databases (i.e., EBSCO (Medline), PubMed, Science Direct, and Web of Science) between January 2011 and May 2022. Out of 86 articles retrieved, seven were selected based on keywords and seven other studies through manual search-five cross-sectional studies, two qualitative studies, one correlational study, one mixed method study, one case-control study, two sections of books, and two educational materials. The findings suggest that preparation and intake of food with modified texture play a necessary role in the safety of swallowing in addition to physical, social, and environmental aspects. Safety was found to be the crucial part of the food texture modification provision besides considering the stress of the caregivers and the nutritional status of individuals with CP. Currently, there are no standard guidelines available pertaining to food texture modification. This led to uncertainties in the dietary provision among caregivers, which may lead to undernourishment. Hence, standard guidelines relating to food texture modification that focuses on food preparation and menus with calorie and nutrient information are timely to be developed.